Determinasi Kepemimpinan Pelayan, Motivasi Kerja, Kepuasan Kerja, Dan Budaya Organisasi Terhadap Kinerja Guru - D. Astuti; K.R.H. Dantes; I.N. Natajaya (Jurnal Administrasi Pendidikan Indonesia, 2021)
This study aims to determine the determination of servant leadership, work motivation, job satisfaction, and organizational culture on teacher performance at SMA Negeri 1 Sukasada. This research is an ex-post facto research. The population in this study were 53 people and the entire population was used as the research sample. The data collection method used in this study was a questionnaire. The data analysis used in this research is product moment correlation, partial correlation, and multiple regression. Data were analyzed using SPSS 16.0 for Windows. The research results are as follows. (1) there is a determination or an effective contribution of 13.08%, (2) there is a determination or an effective contribution of 21.17%, (3) there is a determination or an effective contribution of 24.26%, (4) there is a determination of an effective contribution of 13.69%, and (5) there is a joint determination or contribution of servant leadership, work motivation, job satisfaction and organizational culture on performance by 72.20% for teachers at SMA Negeri 1 Sukasada, Buleleng Regency.